A biological rationale for the disparate effects of omega-3 fatty acids on cardiovascular disease outcomes. (July 2022) - Sherratt, Samuel C.R.; Libby, Peter; Bhatt, Deepak L.; Mason, R. Preston
Highlights: Identified differences in cardiovascular outcome effects of IPE in clinical trials and how this differed from EPA/DHA mixed formulations; Discussed how different n3-FAs, specifically EPA and DHA, interact with the membrane at the molecular level; Compared the effects of n3-FAs on membrane oxidative stress and cholesterol crystalline domain formation during hyperglycemia; Reviewed effects of n3-FA on endothelial function and nitric oxide bioavailability, and the role of n3-FA-generated metabolites in inflammation resolution; Discussed ongoing and future clinical investigations exploring treatment targets for n3-FAs, including COVID-19. Abstract: The omega-3 fatty acids (n3-FAs) eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) rapidly incorporate into cell membranes where they modulate signal transduction pathways, lipid raft formation, and cholesterol distribution. Membrane n3-FAs also form specialized pro-resolving mediators and other intracellular oxylipins that modulate inflammatory pathways, including T-cell differentiation and gene expression. Cardiovascular (CV) trials have shown that EPA, administered as icosapent ethyl (IPE), reduces composite CV events, along with plaque volume, in statin-treated, high-risk patients. Mixed EPA/DHA regimens have not shown these benefits, perhaps as the result of differences in formulation, dosage, or potential counter-regulatory actions of DHA. Indeed, EPA and DHA have distinct, tissue-specific effects on membrane structural organization and cell function. This review summarizes: (1) results of clinical outcome and imaging trials using n3-FA formulations; (2) membrane interactions of n3-FAs; (3) effects of n3-FAs on membrane oxidative stress and cholesterol crystalline domain formation during hyperglycemia; (4) n3-FA effects on endothelial function; (5) role of n3-FA-generated metabolites in inflammation; and (6) ongoing and future clinical investigations exploring treatment targets for n3-FAs, including COVID-19.